Advances in our understanding of the influence of gender on patient outcomes with peripheral arterial disease co-occurring with diabetes. Issue 3 (3rd May 2016) - Paul, Neha; Vuddanda, Venkat; Mujib, Marjan; Aronow, Wilbert S.
ABSTRACT: Peripheral arterial disease is an important predictor of cardiovascular morbidity and mortality. Patients with peripheral arterial disease are at a higher risk of myocardial infarction and stroke. The well-known coronary artery disease risk factors such as diabetes, hypertension, smoking and dyslipidemia are also risk factors for peripheral arterial disease. Hyperglycemia is an important mediator in the pathogenesis of this disease in diabetics, more so in women. The morbidity and poor outcomes associated with peripheral arterial disease in women are emerging. Women are more likely to present at an older age are often asymptomatic and have poorer outcomes with revascularization. Women experience specific sex-related challenges in the various diagnostic methods which could lead to a delay in diagnosis. This is a group which needs close attention and aggressive risk factor modification.